Penyuluhan Hipertensi Kepada Pengunjung Posyandu RW 14 Kelurahan Sumber - Muhamad Afif Nurochman; Wahyu Tri Sudaryanto; Seliana Sinta Debi (Universitas 45 Surabaya, 2024)
Hypertension is a systolic blood pressure of more than 130 mmHg and/or a diastolic blood pressure of more than 80 mmHg. Hypertension is one of the most common chronic diseases characterized by a persistent increase in arterial pressure. More than 1 billion adults worldwide suffer from hypertension, and up to 45% of the adult population is affected by hypertension. Objective: This activity aims to increase public understanding regarding hypertension. Method: Activities with outreach and education using leaflet media. Evaluation using a questionnaire both before counseling and after delivering the material.